Insulin clearance: an underappreciated modulator of plasma insulin concentration. Issue 7 (26th May 2016) - Kim, Sun H; Reaven, Gerald M
Abstract : Plasma glucose concentrations are tightly regulated and maintained within a narrow range in non-diabetic individuals. Maintenance of this physiological state is primarily a function of the ability of the pancreatic β-cells to modify insulin secretion rate (ISR), thus preventing wide-swings in plasma glucose concentrations. As a consequence, and in contrast to plasma glucose concentrations, plasma insulin concentrations vary substantially in non-diabetic individuals. Although differences in ISR are primarily responsible for the variability in plasma insulin concentration, there is increasing evidence that differences in insulin clearance rate (ICR) also play a role in regulation of plasma insulin concentration. The goal of this mini-review is to highlight situations that demonstrate the important role of ICR in both insulin and glucose homeostasis.